Taxonomic novelties in Rhynchospora (Cyperaceae) - Silva Da Silva Filho, Pedro Joel; Trevisan, Rafael; Boldrini, Ilsi Iob (Phytotaxa, 2013)
The genus Rhynchospora Vahl has about 354 species with concentration in tropical America. In Brazil, Rhynchospora is the most abundant genus of the family, with 157 species, of which 40 are considered endemic. With the knowledge obtained in field trips, literature and herbaria reviewed, this work aims to contribute to the taxonomy of the genus Rhynchospora. As main results we highlight the synonymization of Rhynchospora glaziovii and R. floribunda, R. robusta and R. semihirsuta, and R. uniflora and R. biflora. A new description for R. conferta, which is a valid species and has been considered as a synonym of R. robusta, is also presented. During the review, we found a new record to Rio Grande do Sul, R. splendens. A diagnosis of all these species are provided, as well as new lectotypes and neotypes designations.